PHASE TRANSFORMATIONS OF PHOSPHATES DURING SEDIMENTATION AND GENESIS OF PHOSPHORITES - Kholodov V.N. (My University, 2004)
The paper outlines the phosphorus cycle from magmatogenic apatite on continents to hydrogenic phosphorites in seas and oceans. It is established that terrigenous apatite is transformed into hydrogenic forms within weathering crusts, soils, and lowmoors. In arid zones, terrigenous apatite is transported to end water basins, where it is reworked by biogenic-diagenetic processes to hydrogenic phosphates. Various hypotheses of phosphate genesis are critically considered, and it is shown that phosphorite deposits form due to marine interstitial and bottom waters concentrating phosphorus owing to biogeochemical processes and forming phosphate accumulations because of oxidation and alkalization. Phosphatization is a multistage, complex process that occurs under the influence of various biogenic processes.